The Effect of Tiktok Social Media on Learning Achievement of Class IV Students at SDN 101767 Tembung - Miftahul Jannah Manurung; Yosephine Edwina; Ria Renata Ginting; Disah Tri Ananda; Laurensia M. Perangin Angin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Social media is a medium that facilitates collaboration between users who produce content (user-generated content). Currently, the Tiktok application is widely used by students. This study aims to determine how much influence Tiktok social media has on the learning achievement of fourth-grade students at SDN 101767 Tembung. This research is quantitative. The method used in this study is the ex post facto method. The results showed that t(count)> t(table), namely 14.21978769> 2.002272456. This shows that there is a positive correlation or influence between the Tiktok social media variables and learning achievement. From these results, it is clear that there is a positive correlation or influence from Tiktok social media on learning achievement. So, it is said that social media affects the learning achievement of students in class, even though little or no one uses it in the classroom or school environment.